Ophthalmic Treatment and Vision Care of a Patient with Rare Ring Chromosome 15: A Case Report - Lidia Puchalska-Niedbał; Stanisław Zajączek; Elżbieta Petriczko; Urszula Kulik (Hindawi Limited, 2014)
The Aim. Ring chromosome 15 is a very rare genetic abnormality with a wide spectrum of clinical findings. Up to date, about 50 cases have been documented, whereas no reports on ophthalmological treatment of such patients have been published. The aim of this study is not only to describe a new patient, but also, for the first time, to present the results of nonoperative management of divergent strabismus. Material and Methods. We present an amblyopic patient with 46,XX, r(15) karyotype: treated conservatively for exotropia of 60 prism diopters. The management consisted of refractive and prismatic correction, eye occlusion, and orthoptic exercises between the age of 15 months and 8 years. Results. The deviation angle of exotropia was decreased to 10 prism diopters, the visual acuity improved to 1.0 in both eyes (Snellen chart) and the fixation pattern was normal. The prisms enabled permanent symmetrical stimulation of the retina, which lead to a development of normal single binocular vision (Maddox test, filter test, and synoptophore tests). Conclusions. Parental karyotype was normal; the analysis of a three-generation pedigree has shown no genetic abnormalities or pregnancy losses so the child's karyotype anomaly was classified as de novo that is a single occurrence of this type of chromosomal disorder in this family. Strabismus in ring chromosome 15 patients is a difficult condition to manage, although success may be achieved.